Second Cold War : US and Caribbean law and order - Vega, Bernardo (CSIS Americas Program WashingtonUS, 1998)
Examines the new US-Caribbean relationship. Views US policy as largely focussed on 'police issues' such as drugs and illegal immigration. Perceives simularities in a U.S. policy that fought against those 'soft on communism' and a policy that fights against those ' soft on drugs'. Introduces an often overlooked element into the US-Caribbean relationship : that of the Caribbean diaspora.